Intra- and interspecific variability of Mentha arvensis L. and M. Canadensis L. - M. V. Semenova; O. L. Enina; O. V. Shelepova (Вавиловский журнал генетики и селекции)
The identification of plants of the genus Mentha is often difficult due to significant intraspecific polymorphism, intense interspecific hybridization, and ploidy changes. An attempt was made to apply an integrated approach to the study of different parameters of two species: Mentha arvensis L. and M. canadensis L. Eight geographically dispersed populations of Mentha in different regions (European Russia, Khakassia and Far East, Western Ukraine, and Indochina) were studied. Diagnostic morphological characters and compositions of essential oil components were examined, and DNA was analyzed with ISSR markers. The data obtained were statistically processed by cluster, principal component, and principal coordinate analyses. The European and Asian groups of samples were clearly distinguished by the analysis of quantitative parameters of the calyx and leaves, but different methods of data processing produced different results in determining the belonging of the Far Eastern plants to a particular group. Therefore, their taxonomic positions can hardly be determined on morphological grounds. According to the composition of essential oil and ISSR fragments, a group of the genetically, morphologically, and phytochemically closest plants was identified, which included representatives of the populations of the Moscow oblast, Vladimir oblast, Kaluga oblast, the Komi Republic, and Khakassia. All these plants belonged to M. arvensis. Plants collected in the natural flora of the Russian Far East showed a greater resemblance in essential oil composition and ISSR markers to the European group of M. arvensis than to plants from Indochina, which, according to the data obtained, belonged to M. сanadensis. It was shown that a comprehensive study of plant morphological characters, the compositions of essential oil, and ISSR fragments allows one to clarify the species identity and to assess their polymorphism and the degree of kinship between populations. A certain correlation between the data of molecular analysis and the composition of essential oil and, to a lesser extent, their correlation with morphological characters of plants was revealed.